EYL Teachers' Challenges on Professional Development - Hamdani, Beny (JADEs Journal of Academia in English Education, 2022)
The current article discusses English for young learner (EYL) teacher's challenges on professional development (PD) and divides the issues into three parts. The study is based on the experiences of EYL teachers' challenge on PD in teaching English. The article starts by discussing the conceptualization of PD. Next, it delves into model, benefit and characteristics of effective PD. The last part discusses EYL teachers' challenges on PD and its implication. This study has contributed to the research field by providing in-depth insights into Indonesian EYL teachers' challenges on PD. The findings from this study raise EYL teachers' awareness of their own challenges on PD. This article provides a theoretical basis for understanding the flux and the dynamic nature of EYL teachers' challenge on PD for further research. Finally, this paper discusses the limitations of this study and provides suggestions for future research.